Historical dictionary of Kierkegaard's philosophy - Barnett, Christopher B. (Christopher Baldwin), 1976- (Historical Dictionaries of Religions, Philosophies, and Movements Series., 2022)
"Historical Dictionary of Kierkegaard's Philosophy, Second Edition chronicles the life and thoughts of the great Danish thinker Søren Kierkegaard (1813-55). What makes this volume essential is its extensive scope: it provides a glossary of concepts, persons, and places related to Kierkegaard's authorship, from "Absolute" to "Hans Christian Ørsted.""--